An interoperable and immersive simulation as training and procedure design support system in car terminals. (2016) - Nicoletti, Letizia; Padovano, Antonio
Designing efficient operational procedures and training operators to be responsive and consistent with them in a timely manner is critical in many industrial sectors. Indeed, companies strive to achieve increased efficiency in the procedure design process and look for innovative valuable and cost-effective approaches that push operators to reach the plateau of such procedures' learning curve as quickly as possible in order to save money and time. In particular, port terminals, and car terminals specifically, are complex systems because many operations involving coordination problems usually take place. In car terminals, complex procedures must be strictly respected and are regulated by security, reliability, optimisation and synchronisation protocols that each worker has to know and comply with when performing his tasks. Therefore, a consistent and replicable simulation-based framework is proposed for training operators in car terminals in order to improve operator's efficiency and enhance the effectiveness of both training activities and procedure design processes. Cutting-edge technologies are integrated with the proposed system, thus providing the end-user with a full-immersive experience and promoting a human-in-the-loop and hardware-in-the-loop approach.